Medical Imaging 2020: Biomedical Applications in Molecular, Structural, and Functional Imaging 2020
DOI: 10.1117/12.2549052
|View full text |Cite
|
Sign up to set email alerts
|

Fully automated segmentation of the right ventricle in patients with repaired Tetralogy of Fallot using U-Net

Abstract: Cardiac magnetic resonance (CMR) imaging is considered the standard imaging modality for volumetric analysis of the right ventricle (RV), an especially important practice in the evaluation of heart structure and function in patients with repaired Tetralogy of Fallot (rTOF). In clinical practice, however, this requires time-consuming manual delineation of the RV endocardium in multiple 2-dimensional (2D) slices at multiple phases of the cardiac cycle. In this work, we employed a U-Net based 2D convolutional neu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Thus, we believe that accumulation of slight errors on the right side of the heart resulted in a weak correlation of the FAC on the right side in our study. Similar to that reported previously, the low extraction accuracy of the right side of the heart remains a major challenge for automated segmentation based on U-Net CNN, and further work is required in this field [17,[26][27][28]. Nevertheless, we demonstrated that U-Net CNN enables extraction of areas in all the four cardiac chambers, with high accuracy, using 4CH cine CMR images.…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…Thus, we believe that accumulation of slight errors on the right side of the heart resulted in a weak correlation of the FAC on the right side in our study. Similar to that reported previously, the low extraction accuracy of the right side of the heart remains a major challenge for automated segmentation based on U-Net CNN, and further work is required in this field [17,[26][27][28]. Nevertheless, we demonstrated that U-Net CNN enables extraction of areas in all the four cardiac chambers, with high accuracy, using 4CH cine CMR images.…”
Section: Discussionsupporting
confidence: 80%
“…Each image predicted by the developed U-Net CNN contained blood pools that do not correspond to each cardiac chamber. To correct the morphology, the predicted images underwent morphological closing using a 3-pixel radius disk, based on selection of the largest area and as reported previously [17]. The closed images were then binarized by the adapted threshold method [21].…”
Section: Image Post-processingmentioning
confidence: 99%
See 1 more Smart Citation
“…19,20 This has potential to improve clinical workflow, but importantly it is based on volumetric analysis which includes papillary muscles and trabeculations in the ventricular volumes. 20,21 Linear regression analysis showed significant associations of LV and RV volumetric parameters with studied parameters (gender, age, BSA, body weight, and body height). Subsequent multivariable regression analysis demonstrated that body height and body weight showed significant associations with volumetric results.…”
Section: Discussionmentioning
confidence: 97%
“…At present, there have been many researches on automatic heart segmentation, but most of them are carried out on high-quality and well-displayed images such as MRI and CTA (39)(40)(41)(42).This research is carried out on radiotherapy positioning CT, which is the basic image of clinical radiotherapy. The image quality is relatively low and it is difficult to identify the border of the organ.We combined different loss functions into different deep neural networks, and compared their segmentation effects.Tran (43) et al used U-Net-based CNN to segment the right ventricle on cardiac MRI, and obtained an average DSC of 0.9 (95%HD: 5.1mm). In this study, GDL U-Net segmented the right ventricle with an average DSC of 0.912 (95% HD: 4.242 mm), which is relatively better than Tran's segmentation results.In addition, most of the current researches on the automatic segmentation of the heart are single-organ segmentation, and only a few researches on the automatic segmentation of the heart and two ventricles.…”
Section: Discussionmentioning
confidence: 99%